Copepod distribution and biodiversity patterns from the surface to the deep sea along a latitudinal transect in the eastern Atlantic Ocean (24°N to 21°S). (February 2018) - Bode, Maya; Hagen, Wilhelm; Cornils, Astrid; Kaiser, Patricia; Auel, Holger
Graphical abstract: Highlights: Copepod communities were analyzed down to 2000 m in the (sub)tropical Atlantic. In total, 26 families, 79 genera and at least 172 calanoid species were identified. Depth had the strongest impact on copepod community structure. Diversity was highest at 100–200 m in the tropics and 400–700 m in the subtropics. Abstract: Vertical distribution, community structure and diversity of calanoid copepods were studied at six stations along a latitudinal transect from 24°N to 21°S in the eastern Atlantic Ocean, resolving nine discrete depth layers to 2000 m. Total copepod abundances integrated from 0 to 2000 m ranged from 148, 000 to 197, 000 ind m −2 . Usually, abundance and biomass were highest in the upper 100 m, exponentially decreasing with increasing depth. Only at the northern- and southernmost stations, a deeper biomass maximum was observed at 100–200 m and 200–400 m, respectively. In total, 26 families, 79 genera and at least 172 species were identified among calanoid copepods. Although there were certain regional differences in species composition between tropical and subtropical stations from north to south, depth had the strongest impact on the community structure of calanoids, resulting in statistically distinct communities in different depth zones. Maximum diversity of calanoids was observed between 100–200 m in the tropical zone and between 400–700 m in subtropical regions. Various interacting mechanisms such as vast spatial extent of the ecosystem, physical stability, avoidance from predators under dim light, small population sizes and high biologically generated heterogeneity possibly contribute to the biodiversity maxima in the twilight zone.